2013
DOI: 10.1136/bcr-2012-008115
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor (G-CSF): a mediator in endometrial receptivity for a patient with polycystic ovary (PCO) undergoing in vitro maturation (IVM)

Abstract: SUMMARYProliferative and secretory changes at the endometrial lining are the result of a complex intrauterine environment where sex steroid hormones and different local factors play an important role for endometrial thickening. Optimal endometrial thickness reflects an adequate maturation which is a key factor for embryo implantation. Here, we present a case of a woman with polycystic ovary who was treated using in vitro maturation (IVM) techniques. In addition, this patient showed a dyssynchrony between the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…According to this hypothesis, local infusion of PRP that contains several growth factors and cytokines may improve endometrial growth and receptivity. PRP is collected from autologous blood sample, so in comparison to G-CSF, PRP is more accessible and affordable (Gleicher et al , 2011; Lucena & Moreno-Ortiz, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…According to this hypothesis, local infusion of PRP that contains several growth factors and cytokines may improve endometrial growth and receptivity. PRP is collected from autologous blood sample, so in comparison to G-CSF, PRP is more accessible and affordable (Gleicher et al , 2011; Lucena & Moreno-Ortiz, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Authors observed a 19.1% ongoing clinical pregnancy rate and concluded that G-CSF is useful in the treatment of chronically thin endometrium [Gleicher et al 2013]. A case study by Lucena and Moreno-Ortiz [2013] reported an increase in endometrial thickness after infusing 300 ug of G-CSF at the time of oocyte retrieval. Similar results were observed in a nonrandomized clinical trial conducted by Tehraninejad et al [2015] on a group of fifteen infertile women undergoing fresh IVF cycles (infusion of 300 ug/1 mL of G-CSF at the day of oocyte retrieval).…”
Section: Discussionmentioning
confidence: 99%
“…Since 2011, seven studies (Barad et al, 2014;Gleicher et al, 2011Gleicher et al, , 2013Kunicki et al, 2014;Li et al, 2014;Lucena and Moreno-Ortiz, 2013;Zhao et al, 2013) have evaluated the effect of G-CSF on endometrium and IVF outcomes ( Table 3). Consistent with previously reported data (Gleicher et al, 2013;Kunicki et al, 2014), TEM increased significantly after G-CSF treatment in the same cycles.…”
Section: Discussionmentioning
confidence: 99%